2021
DOI: 10.1371/journal.pone.0250156
|View full text |Cite
|
Sign up to set email alerts
|

A 115,000-year-old expedient bone technology at Lingjing, Henan, China

Abstract: Activities attested since at least 2.6 Myr, such as stone knapping, marrow extraction, and woodworking may have allowed early hominins to recognize the technological potential of discarded skeletal remains and equipped them with a transferable skillset fit for the marginal modification and utilization of bone flakes. Identifying precisely when and where expedient bone tools were used in prehistory nonetheless remains a challenging task owing to the multiple natural and anthropogenic processes that can mimic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 122 publications
0
9
0
Order By: Relevance
“…Therefore, future studies should be articulated along two main axes. First, more experimental programs must be implemented to test the criteria suggested to recognize intentionally modified osseous fragments (e.g., Backwell and d'Errico, 2004;Doyon et al, 2021). Such criteria would allow zooarchaeologists and taphonomists to quickly identify faunal remains that should be subjected to a thorough technological analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, future studies should be articulated along two main axes. First, more experimental programs must be implemented to test the criteria suggested to recognize intentionally modified osseous fragments (e.g., Backwell and d'Errico, 2004;Doyon et al, 2021). Such criteria would allow zooarchaeologists and taphonomists to quickly identify faunal remains that should be subjected to a thorough technological analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, when comparing the dimension of the stone tools and the bone fragments with flake removal scars interpreted as expedient tools, a morphometric continuum is demonstrated, which appears to indicate a functional complementarity between the two aspects of material culture. Given the site function, it was hypothesized these bone tools may have been used in butchery and carcass processing activities (Doyon et al, 2021). Collectively, the results from Lingjing suggest we are in presence of a longlasting tradition.…”
Section: Pleistocene Bone Technology In Chinamentioning
confidence: 92%
See 2 more Smart Citations
“…Although the oldest bone tools are found at Olduvai 9 , 10 as early as 2.1 million years ago (Ma) and slightly later between 1 and 2 Ma at sites in southern Africa 11 13 , it isn’t until the later part of the Middle Pleistocene that bone tools become more widespread with examples from sites in the Near East and Europe. Recent studies 14 – 25 have shown that Middle Pleistocene hominins used a variety of antler and bone implements as hammers and anvils to shape and re-sharpen flint tools. The adoption of soft hammers is a significant technological advance that allowed greater precision and refinement in lithic tool production usually associated with later Acheulean handaxes (Mode 2) and Levallois and Mousterian flake tools (Mode 3).…”
Section: Introductionmentioning
confidence: 99%